Some observations on the measurement of haemoglobin A2 and S percentages by high performance liquid chromatography in the presence and absence of α thalassaemia. Issue 3 (27th February 2004) - Head, C E; Conroy, M; Jarvis, M; Phelan, L; Bain, B J
Abstract : Aims: To assess the accuracy and precision of measuring haemoglobin A2 by high performance liquid chromatography (HPLC) in the presence and absence of sickle cell trait, with or without α thalassaemia trait. Methods: The haemoglobin A2 percentage and the haemoglobin A2 plus S percentages were determined by HPLC on 82 normal controls and 78 patients with sickle cell trait, respectively; the α thalassaemia status of each patient was determined by polymerase chain reaction. Red cell indices and haemoglobin A2 and S percentages were compared in patients with two, three, or four α genes. Results: Of the 78 patients with sickle cell trait, 17 were heterozygous for α + thalassaemia (−α 3.7 /αα) and 13 were homozygous (−α 3.7 /−α 3.7 ). Microcolumn chromatography showed that the haemoglobin A2 percentage was slightly, but significantly, higher than normal in sickle cell trait. HPLC determinations of haemoglobin A2 percentage in patients with sickle cell trait are precise but inaccurate, the percentage being appreciably overestimated. The measured haemoglobin A2 percentage is stable for one week, but inaccuracy increases by two weeks in most samples. Despite this inaccuracy, there are significant differences in the HPLC "haemoglobin A2 percentage" between groups of individuals with two, three, and four α genes. Conclusions: Haemoglobin A2 determinations by HPLC are precise but inaccurate. Nevertheless, there are significant differences in the haemoglobin A2 percentage in subjects with two, three, and four α genes. Although there is some overlap between groups, this can be useful, together with the red cell indices, in predicting the likelihood of coexisting α thalassaemia.